2020
DOI: 10.1002/jhbp.781
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the association between bile infection and clinically relevant pancreatic fistula in patients undergoing pancreatoduodenectomy

Abstract: Despite improvements in surgical technique and postoperative management, pancreatoduodenectomy (PD) is associated with high morbidity 1-3. The most frequent causes of morbidity after PD are anastomotic insufficiencies, particularly clinically relevant postoperative pancreatic fistula (CR-POPF). In a recent case series, the reported rates of such conditions ranged from 8.9% to 29.1% 2-7. Previous studies have reported a correlation between bacterial infection and the development of a pancreatic fistula after PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Seven studies [ 16 , 27 , 29 , 32 , 33 , 38 , 39 ] analyzed the relationship of pancreatic duct diameter <3 mm and CR-POPF, involving 12,325 patients. The fixed effects model was used for data synthesis because of a low heterogeneity ( I 2 = 28%) among the 7 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies [ 16 , 27 , 29 , 32 , 33 , 38 , 39 ] analyzed the relationship of pancreatic duct diameter <3 mm and CR-POPF, involving 12,325 patients. The fixed effects model was used for data synthesis because of a low heterogeneity ( I 2 = 28%) among the 7 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship of preoperative chemoradiotherapy and CR-POPF was assessed by 5 studies with 11,128 patients. [20,27,32,34,39] There was a low heterogeneity ( I 2 = 49%), so the fixed effects model was adopted. The pooled data showed that preoperative chemoradiotherapy was a significant protective factor of CR-POPF (OR = 0.68, 95% CI: 0.57–0.81, P < .001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The autodigestive effect of leaky pancreatic juice damages surrounding tissue and encourages infections (39). At the same time, infection can affect the healing of pancreaticointestinal anastomosis and further aggravate the severity of POPF (40). Therefore, in clinical practice, it is necessary to closely detect the bacteria in the drainage fluid when CR-POPF occurred.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] The presence of organ/space infections has also been shown to lead to clinically relevant postoperative pancreatic fistula. 11 Current Centre of Disease Control (CDC) guidelines recommend administration of a first-generation cephalosporin as perioperative antibiotic prophylaxis, 12 whereas the surgical care improvement project advocate the use of second-generation cephalosporin in hepatopancreatobiliary operations. 13 There is widespread heterogeneity regarding the choice of antibiotics amongst hepatopancreatobiliary surgeons worldwide.…”
mentioning
confidence: 99%